An economy-wide analysis of impacts on Taiwan of reducing tariff escalation on agriculture-related products in WTO Doha Round negotiations. Issue 1 (28th January 2014) - Lee, Huey-Lin; Chang, Ching-Cheng; Weng, Yungho; Hsu, Sheng-Ming; Hsu, Shih-Hsun; Chen, Yi-Chieh
Abstract : Purpose: – The purpose of this paper is to assess the degree of tariff escalation in Taiwan's agriculture-related commodities and the economy-wide impact of tariff harmonization. Design/methodology/approach: – A computable general equilibrium model of the Taiwan economy is applied to simulate for the economy-wide impact of three alternative proposals that reduce tariff rates as well as the degree of tariff escalation in agriculture-related products. Findings: – The paper shows that reduction in tariff wedge helps increase social welfare of Taiwan at the expense of some agricultural sectors. Based on the pair-wise comparisons of the three tariff reduction proposals, the scenario where the upstream products have the least reduction would have agricultural sectors fare better than in the other scenarios where more negative impact on output and employment would occur to agricultural sectors. Originality/value: – The paper assesses quantitatively the economy-wide impact of reducing tariff wedges between unprocessed and processed products, which is rarely seen in the literature using a detailed computable general equilibrium model.